Ethical Leadership in Higher Education: Navigating the Dilemma of Academic Freedom vs. Institutional Reputation - Zvavahera, Promise; Svongoro, Paul (Universitas Gadjah Mada, 2026)
Introduction/Main Objectives: This study examines the impact of ethical decision-making by university leadership on academic freedom and institutional integrity in two Zimbabwean universities. Background/Problems: Empirical evidence on how ethical leadership in Zimbabwean higher education institutions manages tensions between academic freedom and institutional reputation remains limited. These challenges are intensified by limited resources, fragile governance frameworks, and government interference, which place pressure on institutional autonomy and leadership decision-making. Novelty: This study positions ethical leadership as a key perspective for understanding the persistent but understudied tension between academic freedom and institutional reputation in higher education institutions. Research Methods: A mixed-methods approach was employed. Data were collected through online interviews via Zoom and Microsoft Teams with eight university leaders and twenty academics (four leaders and ten academics from each institution). In addition, a semi-structured Google Form questionnaire gathered responses from 167 academics across the two universities. Finding/Results: The findings show significant government interference in institutional decision-making, particularly in state universities. Foreign researchers experience greater restrictions than citizens and permanent residents. University leadership often prioritises institutional reputation over academic freedom, limiting open communication and critical inquiry. The private university also lacks formal policies protecting academic freedom. Conclusion: Ethical leadership plays a critical role in addressing these challenges. The study recommends establishing clear ethical frameworks and leadership training programmes to safeguard academic freedom while maintaining institutional integrity.